2006
DOI: 10.3748/wjg.v12.i14.2305
|View full text |Cite
|
Sign up to set email alerts
|

An interesting cause of esophageal ulcer etiology: Multiple myeloma of IgG kappa subtype

Abstract: Multiple myeloma is a neoplasm of mature and immature plasma cells. A 50-year-old woman with lumbago, dysphagia, and left arm pain was presented. Upper endoscopical examination was performed. There was an exudate-covered ulcer in the distal esophagus, located at 30-32 cm from the incisors, covering the whole mucosa. Histopathological examination of the specimens obtained from the lesion showed the involvement of plasma cells consistent with multiple myeloma of IgG kappa subtype. Esophageal involvement of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Multiple myeloma (MM) is a neoplastic plasma cell disorder which usually presents as renal failure, anemia, hypercalcemia, lytic bone lesions, immunodeficiency, pathological fractures, and hyperviscosity. It constitutes 1% of all cancers and 10% of all hematological malignancies [ 1 3 ]. It usually occurs in the seventh or eighth decade of life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple myeloma (MM) is a neoplastic plasma cell disorder which usually presents as renal failure, anemia, hypercalcemia, lytic bone lesions, immunodeficiency, pathological fractures, and hyperviscosity. It constitutes 1% of all cancers and 10% of all hematological malignancies [ 1 3 ]. It usually occurs in the seventh or eighth decade of life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calcemia, Renal dysfunction, unexplained Anemia, and Bone lytic lesions (CRAB). 10 There are reports of MM presenting with an esophageal ulcer. 10 The present case had features of end-organ damage like hypercalcemia, renal dysfunction, anemia, and bony lytic lesions, which led to the clinical suspicion of MM.…”
mentioning
confidence: 99%
“…10 There are reports of MM presenting with an esophageal ulcer. 10 The present case had features of end-organ damage like hypercalcemia, renal dysfunction, anemia, and bony lytic lesions, which led to the clinical suspicion of MM. Bone marrow biopsy with negative monoclonal peak and urine Bence Jones protein helped in ruling out MM.…”
mentioning
confidence: 99%
“…A previous treated patient of kappa-light chain multiple myeloma has been noted to have multilobulated submucosal mass with ulceration at the gastric body [2]. Pehlivan et al reported a rare endoscopic finding of exudate-covered ulcer in the distal esophagus in a 50-year-old woman with dysphagia and the biopsy result showed the involvement of plasma cells consistent with multiple myeloma of IgG kappa subtype [3].…”
mentioning
confidence: 99%
“…Pehlivan et al. reported a rare endoscopic finding of exudate‐covered ulcer in the distal esophagus in a 50‐year‐old woman with dysphagia and the biopsy result showed the involvement of plasma cells consistent with multiple myeloma of IgG kappa subtype [3].…”
mentioning
confidence: 99%